Hypoxia and lipid metabolism related genes drive proliferation migration and immune infiltration mechanisms in colorectal cancer subtyping - Shansong Huang; Huiying Wang; Jiaqing Cao; Qiang Pang (Scientific Reports)
Abstract Hypoxia and lipid metabolism play crucial roles in the progression of colorectal cancer (CRC). However, the specific functions of hypoxia- and lipid metabolism-related genes (HLPG) in CRC and their relationships with patient prognosis remain unclear. Differential expression analysis using the TCGA-COAD and GEO databases identified 117 HLPGs through the intersection of the two gene sets. After univariate Cox regression analysis, 17 prognostically relevant HLPG were identified. Consensus clustering classified CRC samples into two subtypes, and the immune microenvironment differences between them were evaluated. A risk scoring model utilizing seven prognostically significant HLPGs was created and its predictive performance was assessed through survival analysis and ROC curves. Finally, the key genes ITLN1 and SFRP2 were functionally validated in CRC cell lines. HLPG was closely linked to CRC prognosis. Two molecular subtypes were identified: Cluster A, characterized by enriched immune pathways and higher immune infiltration, and Cluster B, associated with improved overall survival. The seven HLPG-based risk scoring model effectively stratified patients into high- and low-risk groups, with high-risk patients exhibiting significantly poorer survival outcomes. Functional studies confirmed that SFRP2 and ITLN1 play essential roles in CRC cell proliferation, migration, and epithelial-mesenchymal transition (EMT). Furthermore, ITLN1 upregulated PD-L1 expression, increasing sensitivity to immunotherapy. Hypoxia was found to promote lipid metabolic alterations by modulating SFRP2 and ITLN1 expression. This study highlights the prognostic significance of HLPGs in CRC and introduces a robust risk scoring model for patient outcome prediction. ITLN1 could be a target for enhancing immunotherapy response in CRC.